1997
DOI: 10.1038/bjc.1997.524
|View full text |Cite
|
Sign up to set email alerts
|

Can cancer cells transform normal host cells into malignant cells?

Abstract: Summary A human prostate tumour cell line, LNCaP C4-2, when injected into athymic male nude mice, produced tumours containing:(1) only human cancer cells similar to those injected; (2) only murine stromal cells containing abnormal chromosome constitutions; or (3) both human prostate cancer cells similar to those injected and the transformed murine stromal cells with altered chromosome constitutions.Karyotypic analysis of murine metaphases from all the host-derived tumours showed mostly pseudodiploid chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 13 publications
6
44
0
Order By: Relevance
“…Furthermore, recent findings suggested that certain functional human genes may be involved in the malignant transformation of stromal cells (49,50). This view is also supported by other investigators (53)(54)(55). However, as shown above, two of the transformed cells cloned in the present study are of mouse origin, and only mouse chromosomes were observed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, recent findings suggested that certain functional human genes may be involved in the malignant transformation of stromal cells (49,50). This view is also supported by other investigators (53)(54)(55). However, as shown above, two of the transformed cells cloned in the present study are of mouse origin, and only mouse chromosomes were observed.…”
Section: Discussionsupporting
confidence: 90%
“…However, as shown above, two of the transformed cells cloned in the present study are of mouse origin, and only mouse chromosomes were observed. However, as reported by Pathak et al (53) and Jacobsen et al (54), it is possible that the tumor cells first fused with the stroma cells, led to loss of the tumor cell chromosomes. It has been argued that stimulation with cytokines such as IL-6, GM-CSF and IL-4 is a potential mechanism underlying the malignant transformation of stroma cells (32,56).…”
Section: Discussionmentioning
confidence: 84%
“…For example, when bone marrow stromal cells are coinoculated with the poorly tumorigenic prostate cancer cell line LNCaP, the prostate cancer cells progress to a more tumorigenic phenotype (20,21,24,25). The enhanced tumorigenicity is the result of changes in genotype and phenotype of both the prostate cancer cells and the host stromal cells (19,22,23,26,27). Interestingly, extracted stromal cells that have been in contact with tumor cells retain the ability to transform nontumorigenic cells, indicating that the phenotypic and genotypic alterations of the stromal cells are permanent (28).…”
Section: Introductionmentioning
confidence: 99%
“…Wherever chromosomal changes take place, there ought to be imposed effects within the cells where they occur; even malignancy is affected by other cells [25,26] as these might become sensitive / prone to mutagenesis. This is not only true for cancer cells but many kinds of chromosomal deviations (structural and or numerical) have been recorded in lower frequencies (2 to 4%) among seemingly normal persons in the population [15,19,[22][23][24].…”
Section: Observations and Commentsmentioning
confidence: 99%